First records, phenology, habitat, and host-plant associations of Macrotera opuntiae (Cockerell) (Hymenoptera: Andrenidae) in Montana - Delphia, Casey; Griswold, Terry (Journal of Melittology, 2021)
Abstract. Macrotera (Cockerellula) opuntiae (Cockerell) is a minute bee oligolectic on cacti and one of the few stone-nesting bee species. We document the first records of M. opuntiae in Montana, USA, a considerable range expansion from where this species was previously known in Colorado. We briefly describe the habitat and host-plant (cacti) associations, and the activity period of M. opuntiae adults in Montana. A new state record for Nebraska and new records for western Colorado are also reported.